STRES KELUARGA: MODEL DAN PENGUKURANNYA - Maryam, Siti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2016)
Family is the smallest unit in the community that has a very strong influence into our life. If the family experiences stress, it will affect the system in the family itself. Dr. Thomas H. Holmes and Dr. Richard H. Rahe give a definition of stress -a complicated condition or situation which can endanger people and has exceeded the resources of the individual to cope. Furthermore, they also develop a stress measuring scale called